Effectiveness of intermittent screening and treatment for the control of malaria in pregnancy: a cluster randomised trial in India. Issue 4 (29th July 2019) - Kuepfer, Irene; Mishra, Neelima; Bruce, Jane; Mishra, Vinit; Anvikar, Anupkumar R; Satpathi, Sanghamitra; Behera, Prativa; Muehlenbachs, Atis; Webster, Jayne; terKuile, Feiko; Greenwood, Brian; Valecha, Neena; et al.
Abstract : Background: The control of malaria in pregnancy (MiP) in India relies on testing women who present with symptoms or signs suggestive of malaria. We hypothesised that intermittent screening and treatment for malaria at each antenatal care visit (ISTp) would improve on this approach and reduce the adverse effects of MiP. Methods: A cluster randomised controlled trial comparing ISTp versus passive case detection (PCD) was conducted in Jharkhand state. Pregnant women of all parities with a gestational age of 18–28 weeks were enrolled. Women in the ISTp group were screened with a rapid diagnostic test (RDT) for malaria at each antenatal clinic visit and those in the PCD group were screened only if they had symptoms or signs suggestive of malaria. All RDT positive women were treated with artesunate/sulfadoxine–pyrimethamine. The primary endpoint was placental malaria, determined by placental histology, and the key secondary endpoints were birth weight, gestational age, vital status of the newborn baby and maternal anaemia. Results: Between April 2012 and September 2015, 6868 women were enrolled; 3300 in 46 ISTp clusters and 3568 in 41 PCD clusters. In the ISTp arm, 4.9% of women were tested malaria positive and 0.6% in the PCD arm. There was no difference in the prevalence of placental malaria in the ISTp (87/1454, 6.0%) and PCD (65/1560, 4.2%) groups (6.0% vs 4.2%; OR 1.34, 95% CI 0.78 to 2.29, p=0.29) or in any of the secondary endpoints. Conclusion: ISTp detected more infections than PCD, but monthly ISTp with the current generation of RDT is unlikely to reduce placental malaria or impact on pregnancy outcomes. ISTp trials with more sensitive point-of-care diagnostic tests are needed.